The story of jumping mouse a native American legend - Steptoe, John 1950- (New York Lothrop, Lee & Shepard Books, 1984)
The gifts of Magic Frog and his own hopeful and unselfish spirit bring Jumping Mouse finally to the Far-Off Land where no mouse goes hungry.
Keywords: Indians of North America -- Folklore. -- Great Plains; Mice -- Folklore